Microbiota composition of the dorsal patch of reproductive male Leptonycteris yerbabuenae. - Osiris Gaona; Daniel Cerqueda-García; Luisa I Falcón; Guillermo Vázquez-Domínguez; Patricia M Valdespino-Castillo; Carla-Ximena Neri-Barrios (PLoS ONE, 2019)
Bacteria and other types of microbes interact with their hosts in several ways, including metabolic pathways, development, and complex behavioral processes such as mate recognition. During the mating season, adult males of the lesser long-nosed agave pollinator bat Leptonycteris yerbabuenae (Phyllostomidae: Glossophaginae) develop a structure called the dorsal patch, which is located in the interscapular region and may play a role in kin recognition and mate selection. Using high-throughput sequencing of the V4 region of the 16S rRNA gene, we identified a total of 2,847 microbial phylotypes in the dorsal patches of eleven specimens. Twenty-six phylotypes were shared among all the patches, accounting for 30 to 75% of their relative abundance. These shared bacteria are distributed among 13 families, 10 orders, 6 classes and 3 phyla. Two of these common bacterial components of the dorsal patch are Lactococcus and Streptococcus. Some of them-Helcococcus, Aggregatibacter, Enterococcus, and Corynebacteriaceae-include bacteria with pathogenic potential. Half of the shared phylotypes belong to Gallicola, Anaerococcus, Peptoniphilus, Proteus, Staphylococcus, Clostridium, and Peptostreptococcus and specialize in fatty acid production through fermentative processes. This work lays the basis for future symbiotic microbe studies focused on communication and reproduction strategies in wildlife.